WEWENANG DAN TANGGUNG JAWAB NOTARIS DAN PPAT DALAM SUATU PERIKATAN - Adlia, Lia Trizza Firgita; Tarring, Anisah Daeng; Soraya, Anugra (Universitas Stikubank, 2024)
Notary and PPAT in Engagement between Debtor and Creditor. This study aims to determine, and analyze the extent of the authority of Notaries and PPATs in Creditor Agreements between Debtors and Creditors and the position of Cooperation agreements between notaries and PPATs with Banks according to Positive Law. This study uses a normative juridical approach. The juridical approach is used to analyze various principles and theories related to the problems studied. The research results show that notaries and PPATs in the credit agreement system between creditors are carried out to provide legal certainty. The role of the notary and PPAT is also as the authorized party to check the collateral in the form of Mortgage to ascertain whether the collateral is valid in the eyes of the law or not. The position of notary and PPAT cooperation agreements with banks according to the Civil Code and the Principles of Freedom of Contract are binding and valid based on applicable regulations.